The Archaeology of The Upper City and Adjacent Suburbs - Steane, Kate (Historic England, 2006)
This volume contains reports on sites excavated in the upper walled city at Lincoln and adjacent suburbs between 1972 and 1987. The project included large-scale excavations which yielded some stunning finds and revealed considerable information about several periods of the city's history. Each site is described in turn, incorporating stratigraphic, artifactual and environmental information, and the common threads are brought together in a general discussion. Structural and artifactual evidence for the post-medieval period also give a flavor of the local life-style in the 16th-18th centuries.